Analisis ’Kala’ Dan ’Aspek’ Dalam Bahasa Jepang (Analisis Kalimat dalam Anime ”Corpse Party Tortured Souls” karya Akira Iwanaga) - Santoso, Gina Apriali; Mohammad, Lutfie Hakim; Hafizha, Fasya (Undiksha Press, 2024)
One of the marker structures in Japanese is tense and aspect. Tense indicates the time of the event or action marked by the verb used at the time of the utterance, while aspect is a way to see the formation of time markers internally in a situation, event, state or process. Tense and aspect are quite complex for Japanese language learners. Therefore, this study will describe some forms of tense and aspect found in the 2013 anime Corpse Party. The purpose of this study is to find out what are the tenses and aspects contained in the Corpse Party anime. Data collection is done using the listening method with the advanced technique of free listening. In the data processing process, it is done using the pragmatic pairing method, which uses the theory of Teramura and Nitta which is presented in an informal method. From the results of the analysis, there are 3 methods of analyzing tense and 4 categories of aspects